Inteligência Competitiva e gestão do conhecimento do cliente : um guia para gestão do portfólio de produto no Sebrae/SE - Santos, Alisson Lima (2023)
This study aims to develop a Product Portfolio Management Guide at Sebrae/SE, based on the principles of Competitive Intelligence and Customer Knowledge Management. It characterized as an applied, exploratory, propositional, and qualitative research. The methodological design is based on Design Science Research and its stages, supported by the use of data collection and analysis instruments such as literature review, integrative systematic review, document analysis, non-systematic observation and content analysis. The object of analysis was Sebrae/SE, a company in which information and knowledge are the main inputs for its processes and products to its clients. To define the objectives of the Guide, an organizational diagnosis was conducted through a SWOT analysis, which revealed the absence of a structured process for managing the company's product portfolio. Through systematic reviews, the main processes that make up models or frameworks of Competitive Intelligence and Customer Knowledge Management, as well as methods and tools for product portfolio management, were identified, allowing the conception of a preliminary version of the Guide's process structure. To further structure it, an intervention was carried out in the company, based on the evaluation of the proposed structure in Sebrae/SE. The result of this application was the creation of the editorial product "Product Portfolio Management Guide at Sebrae/SE," which encompasses the processes of Identification, Selection, Collection, Analysis, Application, Sharing, and Updating. To operationalize these processes, methods and tools were defined, including Product Portfolio Workshop, Customer Knowledge Map, BCG Matrix, Product Portfolio Committee, and Performance Indicators. The results demonstrate the synergy between the approaches of Competitive Intelligence and Customer Knowledge Management and their integrated application in product portfolio management in a knowledge-intensive company.